SELF-COMPASSION, GRIT DAN POSITIVE AFFECT SEBAGAI PREDIKTOR KEBERSYUKURAN MAHASISWA PERAIH BEASISWA BIDIKMISI - Sovi Septania; Rendi Saputra; Sulastri Sulastri (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2020)
Indonesian education has several critical issues relate to education access such as commercial accreditation system in university and education becomes business opportunity (Ramly, 2010). Unfortunately, not all prospective students were born in supported financial condition to fund the university educational needs. One alternative is to look for scholarship opportunities provide by third parties or the government. This scholarship has certain demands for scholarship grantees that often creates pressure which takes a sense of gratitude. Emmons & McCullough (2004) states that factors affecting gratitude include self-compassion, positive affect and grit. The research purpose was to empirically analyze the effect of self-compassion, positive affect and grit on gratitude of Bidikmisi scholarship grantee. The research used quantitative methods with multiple regression analysis techniques with the SPSS 25.0 program. The research instruments use Likert scale model. Results showed that there was a significant positive influence between the independent variables and the dependent variable with total 39.2 % influence. Correlation analysis between its variables explained in the discussion.